New insights into the relationship between mIGF-1-induced hypertrophy and Ca2+ handling in differentiated satellite cells. - Simone Guarnieri; Caterina Morabito; Silvia Belia; Laura Barberi; Antonio Musarò; Giorgio Fanò-Illic; Maria A Mariggiò; Maria A Mariggiò (PLoS ONE)
Muscle regeneration involves the activation of satellite cells, is regulated at the genetic and epigenetic levels, and is strongly influenced by gene activation and environmental conditions. The aim of this study was to determine whether the overexpression of mIGF-1 can modify functional features of satellite cells during the differentiation process, particularly in relation to modifications of intracellular Ca2+ handling. Satellite cells were isolated from wild-type and MLC/mIGF-1 transgenic mice. The cells were differentiated in vitro, and morphological analyses, intracellular Ca2+ measurements, and ionic current recordings were performed. mIGF-1 overexpression accelerates satellite cell differentiation and promotes myotube hypertrophy. In addition, mIGF-1 overexpression-induced potentiation of myogenesis triggers both quantitative and qualitative changes to the control of intracellular Ca2+ handling. In particular, the differentiated MLC/mIGF-1 transgenic myotubes have reduced velocity and amplitude of intracellular Ca2+ increases after stimulation with caffeine, KCl and acetylcholine. This appears to be due, at least in part, to changes in the physico-chemical state of the sarcolemma (increased membrane lipid oxidation, increased output currents) and to increased expression of dihydropyridine voltage-operated Ca2+ channels. Interestingly, extracellular ATP and GTP evoke intracellular Ca2+ mobilization to greater extents in the MLC/mIGF-1 transgenic satellite cells, compared to the wild-type cells. These data suggest that these MLC/mIGF-1 transgenic satellite cells are more sensitive to trophic stimuli, which can potentiate the effects of mIGF-1 on the myogenic programme.